2009
DOI: 10.1007/s00586-009-0985-x
|View full text |Cite
|
Sign up to set email alerts
|

Relevance of the cranioaxial angle in the occipitocervical stabilization using an original construct: a retrospective study on 50 patients

Abstract: We present a retrospective study on a series composed of 50 patients, treated between 1992 and 2006, affected by pathologies of the craniocervical junction. All the patients were treated using an innovative procedure based on a cranial claw made up of low profile hooks, conceived by one of the authors. Advantages of this technique are, to our point of view, a higher resistance to cranial hooks dislodgment, when compared with screw fixation instrumentation, especially in pathological conditions, such as rheumat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 11 publications
0
6
0
Order By: Relevance
“…We measured O-C2 angle, however, because it is much more popular to perform O-C2 fusion than O-C1 fusion, and O-C2 angle has been widely used as a landmark of O-C alignment. 1,7,8,18,19,20 In their previous study, the authors recommended that the O-C2 angle in O-C fusion should be kept at least at more than the preoperative O-C2 angle in the neutral position to prevent postoperative dysphagia and/or dyspnea. 7 Ataka et al showed that most of the OSA in RA patients with an upper cervical lesion is of an obstructive type because of a decreased O-C2 angle and subsequent oropharyngeal stenosis.…”
Section: Discussionmentioning
confidence: 98%
“…We measured O-C2 angle, however, because it is much more popular to perform O-C2 fusion than O-C1 fusion, and O-C2 angle has been widely used as a landmark of O-C alignment. 1,7,8,18,19,20 In their previous study, the authors recommended that the O-C2 angle in O-C fusion should be kept at least at more than the preoperative O-C2 angle in the neutral position to prevent postoperative dysphagia and/or dyspnea. 7 Ataka et al showed that most of the OSA in RA patients with an upper cervical lesion is of an obstructive type because of a decreased O-C2 angle and subsequent oropharyngeal stenosis.…”
Section: Discussionmentioning
confidence: 98%
“…The O-C2 angle indicates the angle between McGregor's line [8] and the line of the endplate of the axis (Fig. 1e, g).…”
Section: Clinical and Radiographic Evaluationmentioning
confidence: 99%
“…Conceptually, the occipitocervical neutral position is the functional and balanced position of the head atop the cervical spine. We considered that patients should [3,[8][9][10]. However, it remains unknown whether dysphagia and/or dyspnea are mostly due to mechanical airway obstruction caused by a non-normal occipitocervical angle.…”
Section: Discussionmentioning
confidence: 99%